Positive mental health literacy and job well-being among palliative care nurses: the mediating effect of job crafting - Haiyang Lin; Cunqing Deng; Zhuoxi Xie; Wenjie Zeng; Yumei Li; Yanping Hao (BMC Psychology)
Abstract Background With rising global demand for palliative care, understanding factors influencing nurses’ job well-being becomes critical for maintaining quality of practice. Palliative care nurses operate within persistently high-stress environments characterized by recurrent exposure to patient suffering and mortality. It is therefore essential to understand how to keep their minds health and well-being. Methods We conducted a cross-sectional study between November 2023 and February 2024. A convenience sample of 205 palliative care nurses was recruited from China. A general characteristics questionnaire, the Positive Mental Health Literacy Scale; the Job Crafting Questionnaire; and the Psychological Well-Being Scale were used to obtain the data. Analyses included hierarchical regression analysis, Pearson correlation analysis, and mediation analysis were also performed to analyze the data, using IBM SPSS25.0 and PROCESS V4.2. Results PMeHL demonstrated conspicuous and positive association with job well-being (r = .548, p < .01) and job carfting (r = .549, p < .01) in palliative care nurses. As demonstrated by mediating analysis, job crafting mediated the association between PMeHL and job well-being, with a partial mediating effect of 0.309 (95% CI [0.146, 0.537]), accounting for 30.15% of the total effect. Conclusion These results identified structural relationships between the 3 variables of PMeHL, job crafting, and job well-being, The PMeHL significantly improves job well-being, with job crafting playing a mediating role. Our findings provided a reference for developing strategies to decrease palliative care nurses’ job stress and burnout in high-stress work environments.